Utilizing the radiometric and seismic methods for hydrocarbons prospecting in the Rancheria sub-basin in Colombia. (October 2018) - Salazar, Sonia; Castillo, Luis; Montes, Luis; Martínez, Fabián
Abstract: An onshore radiometric survey sampled in situ the isotopes U 238, Th 232, K 40, and Rn 222 to build maps of normalized values for each element containing negative and positive radiometric anomalies, which could associate with hydrocarbon deposits in the subsoil. The vertical migration of hydrocarbon, water or other gases would have generated the different isotope anomalies. In four 2D seismic sections of the study area, three on dip direction and another in strike direction, we interpreted unconformities, flooding surface, and maximum flooding surfaces, as well as Cretaceous tops. In structural contour maps made from aforementioned seismic sections, we observe structural highs and structures such as truncations of strata. These structures in-depth coincide with uranium, thorium, potassium and radon anomalies seen on the surface. This oil and gas exploration approach that integrates radiometric and emanometric integrated with seismic prospecting can help to reduce the risk in hydrocarbons projects (however, radiometric anomalies are not uniquely associated with hydrocarbons). This work shows a correlation between radiometric (uranium, thorium, and potassium) and emanometric (radon) data in the surface with structures in the subsurface suck like truncation, that could present hydrocarbon, however, on this sub-basin, there has not been found commercial hydrocarbon. Highlights: The radiometric survey integrated with seismic data can provide evidence of accumulation of hydrocarbons in the subsurface. The anomalies radiometric, and emanometric in the surface can be associated with hydrocarbon deposits in depth, this work shows relationships of surface anomalies of radioelements with high structural and stratigraphic truncations shown in the seismic sections. This is the first work in Colombia, that correlate seismic data with surface radiometric and emanometric anomalies for the hydrocarbons exploration.